Poly-Phthalocyanine–Doped Graphene Oxide Nanosheet Conjugates for Electrocatalytic Oxidation of Drug Residues - Chundu, Prince; Dube, Edith; Zinyama, Ngceboyakwethu P.; Moyo, Mambo; Shumba, Munyaradzi (Frontiers in Chemistry, 2021)
Donor and acceptor phthalocyanine molecules were copolymerized and linked to graphene oxide nanosheets through amidation to yield electrocatalytic platforms on glassy carbon electrodes. The platforms were characterized using transmission electron microscopy (TEM), scanning electron microscopy (SEM), Fourier-transform infrared (FTIR) spectroscopy, UV/Vis spectroscopy, cyclic voltammetry, and electrochemical impedance spectroscopy. The fabricated electrochemical catalytic surfaces were then evaluated toward electrocatalytic detection of ascorbic acid and tryptophan. These were characterized by a wide linear dynamic range and low limits of detection and quantification of 2.13 and 7.12 µM for ascorbic acid and 1.65 and 5.5 µM for tryptophan, respectively. The catalytic rate constant was 1.86 × 104 and 1.51 × 104 M−1s−1 for ascorbic acid and tryptophan, respectively. The Gibbs energy for catalytic reactions was −17.45 and −14.83 kJ mol−1 depicting a spontaneous reaction on the electrode surface. The sensor platform showed an impressive recovery when applied in real samples such as fresh cow milk, in the range 91.71–106.73% for both samples. The developed sensor therefore shows high potential for applicability for minute quantities of the analytes in real biological samples.